Farmer Behaviour as Reasoned Action: A Critical Review of Research with the Theory of Planned Behaviour. (17th October 2020) - Sok, Jaap; Borges, Joao Rossi; Schmidt, Peter; Ajzen, Icek
Abstract: In many countries farmers face pressure to adopt practices to promote sustainability and resilience while ensuring efficient business management to produce food and other agricultural products at reasonable cost. Given a policy context in which voluntary action is preferred over government regulation, understanding farmers' motivation to embrace recommended practices has become a major subject for research. Increasingly, this endeavour is guided by the theory of planned behaviour, a reasoned action approach (Fishbein and Ajzen, 2010). We provide a brief overview of the theory of planned behaviour and an elaboration of good practices in the assessment of the theory's constructs. We systematically review 124 applications of the theory to farmer behaviour on a number of specific review criteria. Based on observations of improper use, we consider theoretical and methodological issues and provide recommendations for research design and data analysis.